Effect of GNP/Ag stretchable conductive ink on electrical conductivity - Salim, Mohd Azli; Mohammad Noor, Norida; Masripan, Nor Azmmi; Md. Saad, Adzni; Akop, Mohd Zaid; Chew, Kit Wayne; Photong, Chonlatee; Feng, Dai (Semarak Ilmu Publishing, 2024)
This research aims to develop and formulate a highly thermal graphene hybridization conductive ink combining graphene nanoparticles (GNP), silver flakes (Ag), and silver acetate (SA) as conductive fillers mixed with chemical and organic solvents. With improved properties, it overcomes the limitations of traditional materials while preserving their beneficial characteristics. The study evaluates how the resistivity and properties of the material change in response to environmental factors such as temperature and humidity and how these changes impact its performance in various applications. To develop a highly thermal graphene hybridization conductive ink, a new formulation of conductive ink was formulated using graphene nanoparticles (GNP), silver flakes (Ag), and silver acetate (SA) as conductive fillers mixed with organic solvents. In order to turn the batch of substances into a powder, they were sonicated and followed by stirring to form the mixture into a powder. Before curing at 250oC for 1 hour, the powder was dripped with organic solvents, 1-butanol, and terpineol and mixed using a thinky mixer machine to form a paste. Using a mesh stencil, the GNP hybrid paste was printed on copper substrates. With a scraper, the hybrid GNP paste was applied to the selected grid (3mm x 3mm) on three selected points of the substrate strip. In order to evaluate the performance, the resistivity of the hybrid GNP conductive ink at room temperature was set as the baseline and compared to the resistivity readings obtained at varying temperatures-humidity levels. GNP hybrid room temperature baseline and GNP hybrid after applying different temperature-humidity were compared in terms of electrical and mechanical properties. The average resistivity measurement at all points of the sample remained stable or decreased as the temperature increased. It demonstrates that the electrical conductivity of the ink degrades significantly as the temperature-humidity increases. This indicates that the ink is able to maintain its structural integrity and properties within certain temperature ranges. This signifies that a hybrid conductive ink has good thermal stability. Future work should investigate the strategies for improving the ink's performance under mechanical deformation, such as the use of additives or novel printing techniques.